2018
DOI: 10.1111/jir.12536
|View full text |Cite
|
Sign up to set email alerts
|

Who's challenging who training for staff empathy towards adults with challenging behaviour: cluster randomised controlled trial

Abstract: This is the first large-scale RCT of a co-produced training course delivered by people with ID. Findings indicated a small positive (but statistically non-significant) effect on increased staff empathy at 20 weeks, and small to moderate effects for staff reported secondary outcomes in favour of the intervention group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Fifteen studies did not specify a timeframe for postintervention measurements or were unclear. 31–33 35–38 40 41 43–52 For example, Hastings et al 37 reported measuring empathy 6 weeks post-randomisation but were not clear how long after the intervention had ended that this measurement was taken. For studies that were explicit, postintervention measures varied between 2 days and 6 months, with the majority of measures taken within 2 weeks of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies did not specify a timeframe for postintervention measurements or were unclear. 31–33 35–38 40 41 43–52 For example, Hastings et al 37 reported measuring empathy 6 weeks post-randomisation but were not clear how long after the intervention had ended that this measurement was taken. For studies that were explicit, postintervention measures varied between 2 days and 6 months, with the majority of measures taken within 2 weeks of the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…They have been assessed mainly in studies focusing on co-delivery training for mental health staff. Among the validated scales adopted, Staff Empathy for people with Challenging Behaviour Questionnaire (SECBQ, [97]) can be mentioned, as well as Borderline Personality Disorder-Cognitive/emotional Attitudes Inventory (BPD-CAI/FAI, [98]). Self-efficacy, defined as the belief in one's ability to succeed in specific situations or accomplish a task, has been measured through other reliable tools and adapted instruments.…”
Section: Outcomes For Professionalsmentioning
confidence: 99%
“…Following the further development work on WCW, a large-scale RCT (Hastings et al, 2018) was undertaken. The primary aim was to assess the effectiveness of WCW to increase the empathy of staff working in residential homes for people with LD compared with a waiting list control group, using a cluster randomised controlled trial design.…”
Section: Evaluation Of Who's Challenging Who?mentioning
confidence: 99%
“…Findings indicated a small positive (but statistically non-significant) effect on increased staff empathy at 20 weeks, and small to moderate effects for staff reported secondary outcomes (e.g., positive empowerment attitudes towards people with LD and CB, increased personal accomplishment at work, and positive work motivation), in favour of the intervention group. Referring to the small change in empathy following the WCW training course, Hastings et al (2018) noted that the study "was not powered to detect such small effect sizes." (p. 807).…”
Section: Evaluation Of Who's Challenging Who?mentioning
confidence: 99%